Manajemen Risiko Kontrak Untuk Proyek Konstruksi - Candra Yuliana (Rekayasa Sipil, 2017)
Construction projects often pose a risk of adverse impact on the cost, time and quality of the project during implementation. The risks are included in the category of dominant risk can be avoided and eliminated. The study was conducted by distributing questionnaires to the expert who competence in the implementation of the project at the Department of Public Works, to determine the risks of any risk identified and the dominant influence of the project. The dominant risk has a risk value between 5 and 25. There are 34 major risks, consisting of 5 unacceptable risk and 29 unacceptable risks. There are 44 action for risk mitigation unacceptable and undesirable.